Web-Based Covid-19 Monitoring Information System - Sonia, Reiny Erica; Hizazi , Achmad; Kusumastuti, Ratih (PT. Hafasy Dwi Nawasena, 2025)
The coronavirus is a positive-sense, enveloped, unsegmented single-stranded RNA virus. The coronavirus is classified under the order Nidovirales and the family Coronaviridae. The structure of the coronavirus has a cubic configuration, with the S protein situated on its surface. Protein S, or spike protein, is a principal antigenic protein of viruses and serves as the primary framework for gene encoding. The S protein facilitates the attachment and entrance of viruses into host cells by its interaction with certain receptors on the host cell surface. Coronaviruses are susceptible to heat and may be efficiently inactivated by disinfectants that include chlorine, lipid solvents at 56 ℃ for 30 minutes, ether, alcohol, peracetic acid, non-ionic detergents, formalin, oxidizing agents, and chloroform. Chlorhexidine is ineffective in neutralizing viruses. COVID-19, often referred to as the coronavirus, started to appear toward the close of 2019, and the daily incidence of infections continues to rise, with fatalities surpassing recoveries. Individuals aged 50 and above are more susceptible to developing Covid-19. The current issue is that the community struggles to monitor information on the growth of the coronavirus. This project aims to construct a web-based COVID-19 monitoring information system to facilitate public tracking of COVID-19 developments in Indonesia and worldwide. The system design methodology employs the PIECES framework (Performance, Information, Economy, Control, Efficiency, and Service) with UML (Unified Modeling Language) tools.